2008
DOI: 10.1007/s11516-008-0028-0
|View full text |Cite
|
Sign up to set email alerts
|

Malmquist index analysis of the dynamic changes in scientific research productivity of some Chinese universities before and after merger

Abstract: This paper describes the dynamic changes in research productivity of Chinese higher education institutions (HEIs) before and after merger with Malmquist index, and decomposes the total factor productivity change index into catching-up effect, scale effect and frontier-shift effect. The main finding is that technological improvement and innovation are important factors to improve scientific research productivity of Chinese HEIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
(3 reference statements)
2
8
0
Order By: Relevance
“…they will merge but have not yet done so) have the lowest average efficiency, while non‐merging universities have average efficiency which is in the middle of those observed for her two groups. These results seem to be largely in line with previous findings for the HE sector based on static models (Hu and Liang, ; Mao et al , ; Johnes, ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…they will merge but have not yet done so) have the lowest average efficiency, while non‐merging universities have average efficiency which is in the middle of those observed for her two groups. These results seem to be largely in line with previous findings for the HE sector based on static models (Hu and Liang, ; Mao et al , ; Johnes, ).…”
Section: Resultssupporting
confidence: 92%
“…In China, a policy of institutional merger was launched in 1992 aimed, in part, at improving efficiency (Yang, ), and has seen more than 400 instances of merging institutions since the 1990s (Cai and Yang, ). Studies evaluating the effect of mergers in China have shown that merging has a positive effect on efficiency and productivity in the first year after merger (Hu and Liang, ; Mao et al , ). In a comparative study of universities in Nordic countries and those in China, the effects of merging on performance (measured by production of publications rather than efficiency) vary by size mix of the merging HEIs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some rare quantitative analyses of the efficiency effects of mergers can be found in the context of Chinese higher education where there have been more than 400 mergers since the 1990s (Cai and Yang 2015). Merging has been found to have a positive effect on efficiency and productivity in the first year after merger but not in the subsequent year (Hu and Liang 2008;Mao et al 2009). In addition a recent study of English higher education uses a panel of data from 1996/97 to 2008/09 to compare the mean technical efficiency (estimated using both SFA and DEA) of merged institutions (of which there are 19 instances) with mean efficiencies of pre-and non-merging institutions.…”
Section: Efficiency and Mergers In Higher Education: A Literature Reviewmentioning
confidence: 99%
“…Nevertheless, some studies have found a quantitative increase in scientific production resulting from mergers, while others (among Chinese research universities) have found little change in measures of research impact (in Ripoll-Soler and de-Miguel-Molina, 2014). One study of 25 merged institutions in China found no important scale effects on research productivity after two years (Hu and Liang, 2008). Mao, Du and Liu (2009) considered 20 merged institutions and found that the mergers somewhat improved knowledge production in humanities and social sciences by 2005, with most improvements coming in the first two years after the merger and then fading awayit is unclear to what extent these improvements relate to short-term government preferences in providing research awards.…”
Section: Research Performancementioning
confidence: 99%